MAIN ASPECTS OF TEACHING ENGLISH AS A SECOND LANGUAGE (KONFERENSIYA, 2025)
This extended article provides a comprehensive examination of the primary aspects of teaching English as a second language (ESL). It explores linguistic development, psychological factors, cultural influences, pedagogical principles, and technological integration. The research emphasizes that effective ESL teaching requires a balanced combination of theory-based practice, exposure to authentic language, and learner-centered instruction. The analysis concludes that the multidimensional nature of ESL learning demands innovative, flexible, and culturally responsive teaching strategies